PENINGKATAN HASIL BELAJAR PAI MELALUI MEDIA AUDIO VISUAL PADA SISWA KELAS IV DI SDN 01 MUNGO - Safitri Safitri; Zulfani Sesmiarni; Rodi Rodi; Becky Sonata (CV. ADIBA AISHA AMIRA, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) of grade IV students at SDN 01 Mungo through the use of audio-visual media. Audio-visual media was chosen because of its ability to present learning materials in a more interesting and interactive way, so that it can motivate students to understand the concepts taught. The research method used is Classroom Action Research (CAR) which consists of several cycles, with each cycle involving the stages of planning, implementation, observation, and reflection. The data collected include the results of student learning tests and observations during the learning process. The results of the study showed a significant increase in student learning outcomes after the application of audio-visual media. The average student score increased in each cycle, indicating that the use of audio-visual media is effective in improving students' understanding and learning outcomes in the PAI subject. Based on these findings, it is concluded that audio-visual media can be an effective learning strategy to improve the quality of PAI learning outcomes in elementary schools.